Cancer antigen-125 and outcomes in acute heart failure: a systematic review and meta-analysis. Issue 2 (26th October 2018) - Li, Ka Hou Christien; Gong, Mengqi; Li, Guangping; Baranchuk, Adrian; Liu, Tong; Wong, Martin C S; Jesuthasan, Aaron; Lai, Rachel W C; Lai, Jenny Chi Ling; Lee, Alex Pui Wai; Bayés-Genis, Antoni; de la Espriella, Rafael; et al.
Abstract : Background: Carbohydrate antigen-125 (CA125) is an ovarian cancer marker, but recent work has examined its role in risk stratification in heart failure. A recent meta-analysis examined its prognostic value in heart failure generally. However, there has been no systematic evaluation of its role specifically in acute heart failure (AHF). Methods: PubMed and EMBASE databases were searched until 11 May 2018 for studies that evaluated the prognostic value of CA125 in AHF. Results: A total of 129 and 179 entries were retrieved from PubMed and EMBASE. Sixteen studies (15 cohort studies, 1 randomised trial) including 8401 subjects with AHF (mean age 71 years old, 52% male, mean follow-up 13 months, range of patients 525.1±598.2) were included. High CA125 levels were associated with a 68% increase in all-cause mortality (8 studies, HRs: 1.68, 95% CI 1.36 to 2.07; p<0.0001; I 2 : 74%) and 77% increase in heart failure-related readmissions (5 studies, HRs: 1.77, 95% CI 1.22 to 2.59; p<0.01; I 2 : 73%). CA125 levels were higher in patients with fluid overload symptoms and signs compared with those without them, with a mean difference of 54.8 U/mL (5 studies, SE: 13.2 U/mL; p<0.0001; I 2 : 78%). Conclusion: Our meta-analysis found that high CA125 levels are associated with AHF symptoms, heart failure-related hospital readmissions and all-cause mortality. Therefore, CA125 emerges as a useful risk stratification tool for identifying high-risk patients with more severe fluid overload, as well as for monitoring following an AHF episode.